Structural biology of endogenous membrane protein assemblies in native nanodiscs. (August 2021) - Brown, Chanelle J.; Trieber, Catharine; Overduin, Michael
Abstract: The advent of amphiphilic copolymers enables integral membrane proteins to be solubilized into stable 10–30 nm native nanodiscs to resolve their multisubunit structures, post-translational modifications, endogenous lipid bilayers, and small molecule ligands. This breakthrough has positioned biological membrane:protein assemblies (memteins) as fundamental functional units of cellular membranes. Herein, we review copolymer design strategies and methods for the characterization of transmembrane proteins within native nanodiscs by cryo-electron microscopy (cryo-EM), transmission electron microscopy, nuclear magnetic resonance spectroscopy, electron paramagnetic resonance, X-ray diffraction, surface plasmon resonance, and mass spectrometry. Highlights: Asymmetric biological lipid bilayers can be solubilized intact using styrene- co -maleic anhydride copolymers. Styrene and stilbene monomer subunits insert into membranes to stabilize nanodiscs. Maleic anhydride-derived subunits engender nanodisc solubility and functionality. Structures of in vivo lipid:protein:ligand assemblies are resolvable in native nanodiscs. Recent progress has led to the concept of memteins as key units of membrane function.